Pelatihan Terapi Endrorphine Massage Pada Ibu Hamil Tm 3 Primigravida Di Rumah Sakit Dr. Sobirin Lubuk Linggau - Danur Azissah; Handi Rustandi; Jipri Suyanto; Mira Damayanti; Emi Pebriani (Jurnal Dehasen Untuk Negeri, 2024)
Universities are the pioneers in organizing the higher education process. A reliable Tri Dharma of Higher Education is the relationship between higher education and society that is established in a hamonis and mutual need. The existence of community service is actually very important for university managers and for the existence of the university itself. In order to carry out the Tri Dharma of Higher Education, the Faculty of Health Sciences, Dehesen University Bengkulu organizes an increase in health knowledge to the community, one of which is community service carried out is "Endrorphine Massage Therapy Training for Pregnant Women TM 3 Primigravida at Dr. Sobirin Lubuk Linggau Hospital". Pregnancy is a series of processes that women will experience which begins with the meeting of eggs and sperm in the ovaries followed by the formation of zygotes then growth and development until the formation of the fetus (Reeder et al, 2011). The span of pregnancy is generally about 280 days or 40 weeks. The pregnancy period is divided into three trimesters (Widatiningsih & Dewi, 2017). During pregnancy, there will be several changes, both physiological changes and psychological changes. These changes are normal for pregnant women because of the body's adjustment to the presence of the fetus in the womb. . Common physiological changes are an enlarged abdomen, active fetal movements, skin hyperpigmentation, enlarged breasts, body posture becomes lordosis (Deswani et al., 2018). Common psychological changes are anxiety, worry, fear, fantasy. anxiety will be increasingly felt especially when the mother enters the third trimester of pregnancy. This is because primigravida pregnant women will face a labor process that she has never experienced before. Protracted anxiety in pregnant women is not impossible to have a bad impact on the mother and fetus. Therefore, the need for Endrorphine Massage Therapy training is expected to increase knowledge to TM 3 Primigravida pregnant women and after this training is expected TM 3 pregnant women can practice Endrorphine Massage Therapy to prevent and control anxiety.